Pemanfaatan Media Pembelajaran Berbasis IT Mahasiswa FKIP Universitas Asahan - Khairun, Nisa; Syafitri , Ely; Wulandari, Suci; Sugesti, Pradita; Indria, Syifa (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
This study aims to explain and analyze the ability of FKIP Universitas Asahan students to utilize IT-based learning media through a case study approach. This research involves selecting a sample of case studies covering various study programs in FKIP with the aim of carefully investigating students' knowledge, skills, and attitudes towards the use of IT-based learning media. Data collection techniques involve interviews, observation, and questionnaire dissemination. This analysis involves a deep understanding and ability of how FKIP Universitas Asahan students integrate and implement how technology benefits the learning process of Asahan University students, as well as what factors affect the use of IT-based learning media. The findings of this study show that the learning media used by students in the form of learning videos is the highest, with answers often getting a percentage of 45%, for the use of PowerPoint media the highest, with solutions often getting a rate of 60%, for using Google Classroom media the highest, with answers often getting a percentage of 40%, and for the use of social media the highest, with solutions often getting a presentation of 85%. Based on these data, it can be concluded that the majority of students show an adequate level of knowledge and skills to utilize technology in the learning process.